Motion-picture spatial-differentiation model - Bokšteflová, Barbora (2012)
The thesis presents a game theoretic model of two directors on a single market. It introduces a variable film type which attains a value from the interval [0,1], where the boundaries expresses the art and the mainstream film, respectively. Each director has opposite preferences over a film type and chooses which type of film to shoot. The director's decision influences the profit function of the other director. The objective of each director is to maximize his profit function. The profit function is the difference of the quadratic audience function and of the cost function. The cost function is the sum of quadratic production cost function and linear disutility cost function which expresses the director's unmeasurable cost issued from the deviation from his most preferred film type. The model therefore includes both the economic and the artistic incentives which influence the directors' decision. We prove that for each pair of profit functions, there exists at least one pure strategy Nash equilibrium. The discussion of possible outcomes is illustrated by an empirical application.